2021
DOI: 10.1039/d1cp01584b
|View full text |Cite
|
Sign up to set email alerts
|

Sign flipping of spontaneous polarization in vapour-deposited films of small polar organic molecules

Abstract: Films of polar molecules vapour-deposited on sufficiently cold substrates are not only amorphous, but also exhibit charge polarization across their thickness. This is an effect known for 50 years, but...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Recent studies have shown that various polar organic molecules spontaneously form highly polar films upon their condensation under UHV conditions at cryogenic temperatures. 7,9,11 Subsequent annealing results in nonreversible depolarization profiles that are remarkably similar to the TP-ΔCPD profiles presented here. In order to explore to what extent the charging effects are general among different molecular films, we have extended our study to the behavior of nonpolar molecular films (V film = 0) composed of dipolar molecules that do not form hydrogen bonding.…”
Section: Charging Of Asw Filmssupporting
confidence: 76%
See 1 more Smart Citation
“…Recent studies have shown that various polar organic molecules spontaneously form highly polar films upon their condensation under UHV conditions at cryogenic temperatures. 7,9,11 Subsequent annealing results in nonreversible depolarization profiles that are remarkably similar to the TP-ΔCPD profiles presented here. In order to explore to what extent the charging effects are general among different molecular films, we have extended our study to the behavior of nonpolar molecular films (V film = 0) composed of dipolar molecules that do not form hydrogen bonding.…”
Section: Charging Of Asw Filmssupporting
confidence: 76%
“…TP-ΔCPD measurements were shown to be beneficial in the study of dielectric properties of thick molecular films (ices), with focus on crystalline and amorphous solid water (ASW), either neutral or charged. In the latter case, the possible effect of the nature of the charging (positive or negative) has not been addressed so far.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have started to focus their attention on fundamental studies of the molecular structure of liquids, amorphous semiconductors, polymer solutions, liquid metals (because of their optical and electrical properties), glassy states of substances, metal vapors, and many other systems. Despite the complexity of studying disordered systems at the microscopic level, so far, significant progress has been achieved in this field. General patterns for a wide class of objects have been identified, and the methods for the theoretical analysis of disordered systems have been improved. …”
Section: Introductionmentioning
confidence: 99%